Sustainable urban planning from an economic and financial perspective - Emília Malcata Rebelo (2014)
In this communication are reported the assumptions, methodology, outcomes and conclusions of a research carried out within the scope of the revision of the Land, Territorial Ordinance and Urbanism Act, currently under way in Portugal. This is a deep revision, and it points out the importance of the economic and financial sustainability of urban development operations for municipalities. Land values rise as a result of territorial planning decisions. Thus a planned public intervention is required in order to assure these surplus values are allocated for the populations social interest. Despite the existence of different kinds of land policies, the fiscal-based ones affect the most the market and land uses, and may substantially influence planning goals achievement. Land taxation aims at assuring a source of income to public administration; redistributing welfare so to grant land its social function; giving back to society the land surplus values that accrue from planning decisions and public investments; and increasing the provision of land for urban development. In order to recover part of the surplus values engendered by urban planning decisions, herein is proposed a new territorial management instrument, applied at the Municipal level. It consists in charging a 20% fee on the land value increase (surplus-value) that accrues from concrete building capacity/m 2 assigned by plans to specific urban interventions. This fee will, later on, be used by the municipality on behalf of social purposes. The current proposal is applied, as a case study, to the Urban Development Plan of the Planning Unit 11 of the municipality of Lagoa, located in the Algarve (Portugal). The methodology pursued in the current study consists in the computation of the building capacity/m 2 , and of the surplus values and corresponding 20% fee that accrue from the establishment of that plan, to be charged to promoters and builders, in order to recover part of their unearned increments. This innovative territorial management instrument strengthens municipals economic and financial sustainability, clears up the origins and applications of municipal funds, and ensures that the surplus values engendered by plans are pointed to social purposes and not to specific private interests. The application of this urban fee may be easily extended to other municipalities, as it is founded on information and methodologies that stand inter-municipal comparisons. Besides, this kind of study supports municipal decisions on both urban development and economic-financial issues, in an integrated and sustainable way.